2017
DOI: 10.1073/pnas.1708414115
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in colloquium speakers at top universities

Abstract: Colloquium talks at prestigious universities both create and reflect academic researchers' reputations. Gender disparities in colloquium talks can arise through a variety of mechanisms. The current study examines gender differences in colloquium speakers at 50 prestigious US colleges and universities in 2013-2014. Using archival data, we analyzed 3,652 talks in six academic disciplines. Men were more likely than women to be colloquium speakers even after controlling for the gender and rank of the available spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
158
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 21 publications
5
158
0
4
Order By: Relevance
“…Several papers have investigated the representation of women at scientific conferences, however, we have only identified one that focused on invited speakers at universities (12). In their study, Nittrouer et al, examined 3,652 talks at 50 U.S. institutions in 2013 - 2014 and found that women faculty are less likely to be invited speakers, despite similar acceptance rates (12). We have not been able to identify any publications examining scientific speaker diversity beyond gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have investigated the representation of women at scientific conferences, however, we have only identified one that focused on invited speakers at universities (12). In their study, Nittrouer et al, examined 3,652 talks at 50 U.S. institutions in 2013 - 2014 and found that women faculty are less likely to be invited speakers, despite similar acceptance rates (12). We have not been able to identify any publications examining scientific speaker diversity beyond gender.…”
Section: Discussionmentioning
confidence: 99%
“…Invited seminar series are common within biomedical departments across the United States (12). Usually, seminar series’ consist of faculty members selecting a scientist from another institution to visit their university and present their research, as well as meet with other faculty members and trainees.…”
Section: Introductionmentioning
confidence: 99%
“…49,80 Women's CVs are less likely to include prestigious invited talks. 4,[42][43][44] The leadership credentials of women in health research may also be constrained by broader societal tendencies in which women receive negative responses for being ambitious 81 or exerting control as leaders. [82][83][84] Research suggests that women must choose between being seen as a competent leader or being liked, 82,83 which complicates career advancement within academia, where leadership positions often depend on colleagues' endorsements.…”
Section: Discussionmentioning
confidence: 99%
“…38 Papers 39 and conference abstracts 40 led by women are accepted more frequently when reviewers are blinded to the identities of the authors. Women are underrepresented as invited speakers at major conferences, 4 prestigious universities, 41 and grand rounds. 42,43 When women are invited to give these prestigious talks, they are less likely to be introduced with their formal title of Doctor.…”
Section: Introductionmentioning
confidence: 99%
“…The participation in these scientific events create visibility for researchers and open networking opportunities, with potential to kick start projects or even obtain jobs. A series of studies has shown that in these situations, there is a bias against selecting women to be scientific speakers (7)(8)(9)(10)(11)(12). However, the trends are positive with American Society for Microbiology General Meeting declared speaker gender balance in 2015 (13), and around 40% female invited speakers at major virology conferences in 2017 (7).…”
Section: Introductionmentioning
confidence: 99%